2018
DOI: 10.4103/ijoy.ijoy_62_16
|View full text |Cite
|
Sign up to set email alerts
|

Study to evaluate the changes in polycystic ovarian morphology after naturopathic and yogic interventions

Abstract: Background:Polycystic ovarian syndrome (PCOS) is one of the commonest endocrine disorders in women, with a prevalence ranging from 2.2% to 26% in India. Patients with PCOS face challenges including irregular menstrual cycles, hirsutism, acne, acanthosis nigricans, obesity and infertility. 9.13% of South Indian adolescent girls are estimated to suffer from PCOS. The efficacy of Yoga & Naturopathy (Y&N) in the management of polycystic ovarian syndrome requires to be investigated. Aims: The aim of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Moreover, this study showed significant improvement in TG levels after intervention with exercise, whereas there were no changes in the levels of other metabolic parameters with this intervention. Yoga is an alternative exercise activity that might be effective in improving anxiety and mood of adolescence [47], and ovarian morphology in PCOS adult women [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study showed significant improvement in TG levels after intervention with exercise, whereas there were no changes in the levels of other metabolic parameters with this intervention. Yoga is an alternative exercise activity that might be effective in improving anxiety and mood of adolescence [47], and ovarian morphology in PCOS adult women [48].…”
Section: Discussionmentioning
confidence: 99%
“…Yoga may be a helpful practice to integrate as a regular workout. Studies are done to validate its benefits for androgens and insulin response [ 34 ], which for all intents and purposes is fairly significant. Some lifestyle adjustments are known to help the symptoms and mental well-being of PCOS patients.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, Ram Nidhi et al found that a 12-week holistic yoga program was significantly better than a physical exercise program in reducing anxiety symptoms for adolescents with PCOS [ 116 ]. Ratnakumari et al also reached a similar conclusion that yoga is efficient in bringing about beneficial changes in polycystic ovarian morphology and speculated that a longer intervention might require to regulate menstruation [ 117 ].…”
Section: Tai Chi Yoga and Qigongmentioning
confidence: 99%